Europe/Africa Cooperation - Esteves, Hermínio (2014)
When we refer to cooperation in economics and sociology, we consider a form of collaboration between individuals or organizations with a view to attaining common objectives in accordance with agreed procedures or methods. Cooperation may also be a form of collaboration between states that seek to achieve particular results in close partnership, and thus minimizing the costs, efforts and resources that each would need to use.